Semi-active tuned mass damper building systems Design. - Chey, Min-Ho (Earthquake engineering & structural dynamics.)
Passive and semi-active tuned mass damper (PTMD and SATMD) building systems are proposed to mitigate structural response due to seismic loads. The structure's upper portion self plays a role either as a tuned mass passive damper or a semi-active resetable device is adopted as a control feature for the PTMD, creating a SATMD system. Two degree of freedom analytical studies are employed to design the prototype structural system, specify its element characteristics and effectiveness for seismic responses, including defining the resetable device dynamics. The optimal parameters are derived for the large mass ratio by numerical analysis. For the SATMD building system the stiffness of the resetable device design is combined with rubber bearing stiffness. From parametric studies, effective practical control schemes can be derived for the SATMD system. To verify the principal efficacy of the conceptual system, the controlled system response is compared with the response spectrum of the earthquake suites used. The control ability of the SATMD scheme is compared with that of an uncontrolled (No TMD) and an ideal PTMD building systems for multilevel seismic intensity.